2018
DOI: 10.23958/ijssei/vol02-i07/01
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Traumatization among Professional Caregivers and Support Staff in Selected Hospices in Kenya

Abstract: Hospice workers are constantly exposed to the trauma experienced by the clients they interact with daily in their work settings. The purpose of the current study was to determine the prevalence of vicarious trauma (VT) among the hospice caregivers in selected hospices in Kenya. A tool adapted from Vicarious Trauma Scale was utilized to assess prevalence and levels of vicarious trauma among the participants. A brief questionnaire was also was used to obtain demographic information of the participants. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Nurses, who have close contact with traumatized individuals, are at high risk of developing vicarious trauma due to their emotionally demanding job that requires intense emotional involvement and significant emotional labor. Research has shown that different groups of nurses, including oncology nurses (Liu, 2018), forensic nurses (Newman et al., 2019), emergency nurses (Cowgur, 2006), psychiatric nurses (Spinelli, 2011), midwives (Oğlak & Obut, 2020), hospice nurses (Musili et al., 2022), correctional health nurses (Munger et al., 2015), COVID‐19 frontline nurses (Li et al., 2020) and sexual assault nurse examiners (Raunick et al., 2015), have all experienced varying degrees of vicarious trauma. Moreover, nurses impacted by vicarious trauma may experience a range of physical and mental health challenges, including nightmares, insomnia, depression, anger, social withdrawal, feelings of helplessness, as well as changes in their beliefs and worldview (Maier, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses, who have close contact with traumatized individuals, are at high risk of developing vicarious trauma due to their emotionally demanding job that requires intense emotional involvement and significant emotional labor. Research has shown that different groups of nurses, including oncology nurses (Liu, 2018), forensic nurses (Newman et al., 2019), emergency nurses (Cowgur, 2006), psychiatric nurses (Spinelli, 2011), midwives (Oğlak & Obut, 2020), hospice nurses (Musili et al., 2022), correctional health nurses (Munger et al., 2015), COVID‐19 frontline nurses (Li et al., 2020) and sexual assault nurse examiners (Raunick et al., 2015), have all experienced varying degrees of vicarious trauma. Moreover, nurses impacted by vicarious trauma may experience a range of physical and mental health challenges, including nightmares, insomnia, depression, anger, social withdrawal, feelings of helplessness, as well as changes in their beliefs and worldview (Maier, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses providing direct patient care have reported higher levels of vicarious trauma than nurses predominantly in nonclinical roles (Peacock, 2023). Individuals may also have a higher risk of developing vicarious trauma if they have a history of personal trauma (Leung et al, 2022; Maguire & Byrne, 2016; Musili et al, 2022; Vrklevski & Franklin, 2008). Other factors influencing the development of vicarious trauma include professional experience and social support (Michalopoulos & Aparicio, 2012).…”
mentioning
confidence: 99%